ВОЗМОЖНОСТИ ИСПОЛЬЗОВАНИЯ ИСКУССТВЕННОГО ИНТЕЛЛЕКТА В АКУШЕРСТВЕ И ГИНЕКОЛОГИИ - Litvinova, Елена Валерьевна; Noskova, Oksana Vladimirovna (Mother and Baby in Kuzbass, 2026)
The purpose of the work – researching the potential applications of artificial intelligence in obstetrics and gynecology.Materials and methods of work. The search for scientific information was conducted using domestic and foreign Internet resources such as Google Scholar, PubMed, Medscape, Scopus and Web of Science databases, etc.; as well as on the websites of international medical organizations using specific keywords: artificial intelligence, the use of artificial intelligence in obstetrics and gynecology, natural language processing models, artificial intelligence systems, ChatGPT, and telemedicine in obstetrics and gynecology. The search covered a period of 10 years.Results. The effectiveness of artificial intelligence based on natural language processing models in various areas of obstetrics and gynecology has been proven. The possibilities of artificial intelligence for perinatal medicine and gynecological oncology have been identified, as well as in the field of cardiotocographic analysis based on artificial intelligence for intrapartum fetal monitoring in the direction of detecting premature births.The effectiveness of artificial intelligence in the field of reproductive therapy (for predicting pregnancy after in vitro fertilization and identifying the most viable oocytes and embryos with a high probability of pregnancy) has been proven.The effectiveness of artificial intelligence for assessing prognoses in patients with ovarian cancer has been confirmed (the ability to predict fetal survival with an accuracy of up to 97% has been proven) and for predicting the effectiveness of a particular type of therapy depending on the diagnosis. The capabilities of artificial intelligence for creating models capable of diagnosing early ovarian cancer and for analyzing precancerous images of the cervix have been identified.In addition, it has been shown that in obstetric surgery, the use of physical artificial intelligence is more effective than virtual intelligence (it helps to reduce the duration of the operation and increase accuracy, which leads to a decrease in the number of surgical problems and complications).At the same time, the effectiveness of using artificial intelligence in telemedicine to monitor patients remotely, tracking and regulating their condition using wearable devices connected to artificial intelligence systems, has been determined.Conclusion. Thus, the use of AI in medicine and specifically in obstetrics and gynecology has a number of proven important advantages. However, further study is needed to improve and mitigate existing risks in order to enable deeper integration into practical medical practice.
Keywords: artificial intelligence; natural language processing models; artificial intelligence systems; ChatGPT